Teaching comprehension strategies : all readers need - Outsen, Nicole; Yulga, Stephanie (New York : Scholastic, 2002)
"Mini-lessons that introduce, extend and deepen key reading skills and promote a lifelong love of literature."--Cover
Primary
Keywords: Reading (Elementary); Though and thinking -- Study and teaching (Elementary); Children -- Books and reading